Single and repeated high-level blast, low-level blast, and new-onset self-reported health conditions in the U.S. Millennium Cohort Study: An exploratory investigation - Jennifer N. Belding; Jennifer N. Belding; Claire A. Kolaja; Claire A. Kolaja; Rudolph P. Rull; Daniel W. Trone (Frontiers in Neurology, 2023)
IntroductionAlthough previous research suggests that overpressure exposure from either high-level blast (HLB) or low-level blast (LLB) are harmful to health, to date no large-scale studies with representative samples of military personnel have utilized prospective designs and self-reported measures to examine the relationships between blast exposure and health conditions. To address these limitations, this analysis of data from the Millennium Cohort Study (MCS), the largest and longest running study of U.S. service members and veterans, examined (1) whether single or repeated HLB exposure is associated with self-reported diagnoses of illness and injury, (2) whether repeated HLB is associated with greater risk than single HLB, (3) potential adverse consequences of LLB exposure using military occupation as a proxy, and (4) the combined effects of single or repeated HLB and LLB exposure.MethodMCS participants who completed the 2011–2013 survey (N = 138,949) were classified as having been exposed to “no,” “single,” or “repeated” HLB exposure, and into low or high risk of exposure to LLB based on occupation. Participants self-reported diagnosis of 45 medical conditions; newly reported diagnoses were regressed on single and repeated (vs. no) HLB, occupational risk of LLB, and relevant interactions using logistic regression.ResultsSingle and repeated HLB were associated with new onset of 25 and 29 diagnoses, respectively; repeated HLB exposure was associated with greater risk than single HLB exposure for five diagnoses (e.g., PTSD, depression). Occupational risk of LLB was associated with 11 diagnoses (e.g., PTSD, significant hearing loss). Additionally, 14 significant interactions were detected across 11 diagnoses.DiscussionFindings suggest that overpressure exposure (including single HLB, repeated HLB, and occupational risk of LLB) may increase the risks of self-reporting clinical diagnoses of PTSD, hearing loss, chronic fatigue syndrome, neuropathy-caused reduced sensation in the hands and feet, depression, vision loss, sinusitis, reflux, and anemia. Furthermore, the combination of HLB and LLB exposure may be associated with greater risk of migraines, PTSD, and impaired fecundity. These findings provide further evidence of the potential adverse consequences associated with overpressure exposure and underscore the necessity of public health surveillance initiatives for blast exposure and/or safety recommendations for training and operational environments.